(untitled) (Revista Científica Compendium, 2023)
The management of historical centers (HCs) in Latin America is formed according to parameters established by the United Nations Educational, Scientific and Cultural Organization (UNESCO). This entity granted legitimacy to HCs, promoted their recognition, and advocated for parameters of action for their development, preservation and consolidation. This led to an interest in a documentary and bibliographic approach, based on institutional historical analysis, of the forms of sustainable management of HCs in Latin America, based on recognized experiences. The conclusions reveal the existence of intervention criteria that point out towards the new paradigm of sustainability, leaving open the possibility of doing research, in the case of the HCs of Venezuela, particularly HC Barquisimeto.